"But I Wanted to Appear Happy": How using Arts-Informed and Mixed Methods Approaches Complicate Qualitatively Driven Research on Culture Shock. Issue 2 (April 2015) - Shannon-Baker, Peggy
The study of culture shock has been limited in terms of the use of mixed methods research and arts-informed approaches. The purpose of this research was to expand upon the understanding of culture shock through the use of a mixed methods research design that included arts-informed, qualitative, and quantitative procedures. This study used a concurrent parallel design where all three data types were collected simultaneously, analyzed separately, and then analyzed together. It is based on an information-rich sampling of 10 undergraduate students participating in a short-term study abroad program based in the United States of America that traveled to a South American country. All data were collected throughout the duration of the program: self-portraits and explanatory artist statements, open-ended reflective journals, and responses to a modified version of the Revised Sociocultural Adaptation Scale. The analyses of each of these sets of data (i.e., the initial analysis stage) revealed a complexity of emotions that students experienced as part of their culture shock, the impact of interacting with others, and their heightened experience of culture shock upon returning home. The integration of these findings resulted in a reconsideration of the qualitative data to highlight the importance of interactions with locals while abroad as being particularly important to alleviate culture shock. The article concludes by considering the implications of the arts-informed data and the use of a mixed methods research design for the interpretation of the qualitative data and for qualitative researchers in general.